Language Death - Crystal, David (Cambridge University Press, 2011)
"The rapid endangerment and death of many minority languages across the world is a matter of widespread concern, not only among linguists and anthropologists but among all concerned with issues of cultural identity in an increasingly globalized culture. By some counts, only 600 of the 6000 or so languages in the world are 'safe' from the threat of extinction. A leading commentator and popular writer on language issues, David Crystal asks the fundamental question, 'Why is language death so important?', reviews the reasons for the current crisis, and investigates what is being done to reduce its impact. The book contains not only intelligent argument, but moving descriptions of the decline and demise of particular languages, and practical advice for anyone interested in pursuing the subject further." -- Library of Congress.